MMQuiz: multi modal human computer interaction-based online assessment system. (2018) - Vairamuthu, Subbiah; Anouncia, S. Margret
Ever changing computing techniques and novel innovations in the education system plays a major role for the way any institutions prefer to adopt now-a-days. All the varsities and institutions started transferring their mode of education from traditional class room-based to internet-based online. Part of these processes, the way how students can be assessed online also plays a major role. In this work, a framework has been proposed which was implemented so as to enable the physically challenged students to efficiently utilise to complete their online-based assessments. Though many voice-based browsers existed, they were all far from reality. Several frameworks were designed for specified objectives like interactive assessment whilst they supported generic features like browsing and mailing. Any individual who may be able to communicate via speech may utilise our proposed framework. The same framework could be employed in any varsities or institutions to conduct their speech-based assessments online.